Educational needs and preferences of young European clinicians and physician researchers working in the field of rheumatology. Issue 2 (27th July 2016) - Beyer, Christian; Ramiro, Sofia; Sivera, Francisca; Mandl, Peter; Machado, Pedro M; Ospelt, Caroline; Moltó, Anna; Radner, Helga; Iagnocco, Annamaria; Bijlsma, Johannes W; Lundberg, Ingrid E
Abstract : Objectives: To understand the educational needs and preferences of young clinicians and physician researchers in the field of rheumatology in Europe. Methods: An international online survey was performed as a joint venture of ESCET and EMEUNET. The survey assessed the acceptance of and the access to the current European League Against Rheumatism (EULAR) educational portfolio, as well as the unmet educational needs and learning preferences among individuals below the age of 40 years working in rheumatology in Europe. Results: Among 568 European clinicians and physician researchers, 65% indicated that the existing EULAR educational portfolio adequately covers their educational needs. Within the EULAR portfolio, the online course on rheumatic diseases and the postgraduate course were the most appreciated. Participants were very much in favour of new educational courses on imaging techniques, and 63% of participants indicated a particular interest in musculoskeletal ultrasound. A strong interest in refresher (60%) and general review (55%) courses was observed. Lack of funding was considered the major obstacle to participating in existing EULAR programmes. Finally, participants showed diverse preferences regarding learning modalities with common interests in live courses and conferences. Conclusions: EULAR's training opportunities are well appreciated among young clinicians and physician researchers in rheumatology. The results from this survey will help to develop EULAR's future educational portfolio.